Localización y dimensionamiento óptimo de dispositivos SVC para la compensación de potencia reactiva en SEP - Jácome Ávila, Daniel Ángel (2017)
In this article presents an optimization and location model for an electric power system, with a multi-objective mathematical model to solve the problem of voltage variations giving solution with a reactive power compensation with FACTS SVC devices, Same way the optimal location of the same. The mathematical model was developed in the GAMS tool with the ability to find the appropriate location and at the same time to size the optimum capacity of each SVC device, minimizing costs, losses and the voltage deviation index, through an analysis of the electrical system of Power with the variations of voltage in their nodes having greater incidence in the nodes with loads, optimizing with the objective functions and the necessary restrictions, in this way to have a more stable and reliable electrical system for the consumer with the use of SVC devices achieving The lowest possible costs benefiting the user.